To the Headsprings of Greater India: Comprehension of Ethno-Cultural Substratum of the Civilization by the Bengal Renaissance Thinkers - Skorokhodova, Tatiana G. (Философия и культура, 2025)
Reflection on the headsprings of Indian civilization was an essential component in the process of self-cognition that developed in intellectual life of national-cultural renaissance of British India in XIX – early XX centuries. The Bengal Renaissance intellectuals were the first who began to ‘gather India’, namely to substantiate her cultural, civilizational and socio-historical entity despite a diversity of peoples, regional cultures and social orders. Thinking about an internal unity of India, Bengal thinkers searched for to answer the question on ethno-cultural substratum of the ancient civilization, and about the unity of the North and the South of India. The theme of article is depicted neither in Russian, nor in foreign Indian studies. Based on original sources, the reconstruction of the comprehension process of the theme in the intellectual history of the epoch. Based on hermeneutic analysis of the texts with the interpretations of ethno-cultural substratum in Indian civilization by Rajendralal Mitra, Romesh Chunder Dutt, Swami Vivekananda, and Jadunath Sarkar, the authors reconstructs the evolution of comprehension the country’s inner unity. For the first time in Russian philosophical Indology, the process of unity comprehension is described in its substratum as ‘Aryan’ by Rammohun Roy, the interpretations were continued by the discovery of autochthonous Dravidian (Tamil) component as an important and indefeasible the Own–Other. Criticizing religious-nationalist idea of Arian ancient age, Rabindranath Tagore offered the idea of Greater India (Māhabhāratvarṣa), and the each people participate to create her. The understanding of Indian civilization substratum as the result of Aryan and autochthonous interaction permitted to correlate the North and the South of India, to substantiate to point out their unification into a civilizational integrity as historically established and real, to substantiate its real unity, and to create the idea of a solid foundation for cultural, spiritual and social unity of India from Ancient to Modern age, to which it is possible to appeal as having proven its viability.